(untitled) (Medical Forum Monthly, 2023)
Objective: The aim of the research was to find out the frequency of periodontal diseases in adolescents undergoing fixed orthodontic treatment. Study Design: A Descriptive Cross-Sectional study. Place and Duration of Study: This study was conducted at the Department of Orthodontics & Periodontology, de’Montmorency College of dentistry, Lahore from 2.2.2021 to 30.1.2022. Materials and Methods: Adolescents, aged 12 to 18 years, undergoing fixed orthodontic treatment were selected by purposive sampling type method. Those orthodontic patients were selected who got no active periodontal issues at or before start of orthodontic treatment. The patients having any periodontal issues, medical disorders or systemic diseases were excluded from the study. Selected patients were examined for periodontal diseases and status at 6th month following orthodontic treatment, using World Health Organization (WHO) oral health assessment proforma. The frequency of periodontal diseases and its percentage was determined. Parameters such as bleeding on probing, probing pocket depth, gingival recession and presence of inflammatory gingival enlargement. The sample size was 50 adolescents undergoing fixed orthodontic treatment. Results: The frequency of bleeding on probing was found to be 70%. 58% patients had at least 1mm gingival recession and 36% cases had inflammatory gingival enlargement and presence of pseudo pockets. Conclusion: The high frequency (70%) of bleeding on probing and 36% inflammatory gingival enlargement in adolescents undergoing fixed orthodontic therapy suggests that there is dire need to focus on oral hygiene care and oral hygiene practices for orthodontic patients undergoing fixed type of orthodontic therapy.